Utilization of Nephelium lappaceum (Rambutan) waste as biosorbent for heavy metals and dyes: a review - Rahmadani, Suci; Putra, Rizky Zalmi; Sari, Trisna Kumala; Away, Romy Dwipa Yamesa (Journal of Natural Sciences and Mathematics Research, 2023)
Pollution of environmental streams and ecosystems is rising. One of the sources of water contamination is the wastewater from the textile, plastics, and mining sectors, which contains both organic and inorganic pollutants. Heavy metals and dyes in wastewater must be treated before disposal to protect the aquatic environment and human health. Due to its effectiveness, low cost, and simplicity of use, biosorption has emerged as a wastewater treatment option. Rambutan waste, in particular, is promising for commercial usage due to its extensive availability and efficiency. In this article, we review the usage of natural rambutan peels, seeds, leaves, and stems for the biosorption of water contaminants. We discuss the factors that influence pollutant removal. A pH of 6 to 12 is advantageous for cationic pollutant removal, whereas a pH of less than 5 is appropriate for anionic pollutant removal. More significant concentrations of pollutants generally result in lesser removal, whereas higher doses of biosorbent result in higher removal. The ideal adsorption contact time for rambutan peels and seeds was less than an hour. We also discuss the isotherms of the adsorption process.